Geographic Information System of Early Childhood School Mapping Using Android-Based Dijkstra Algorithm - Rasna, Rasna; Irjii Matdoan, Moh Rahmat; Yuntina, Lily; Salat, Junaidi; Setiawati, Eka (Malikussaleh University, Aceh, Indonesia, 2024)
The PAUD school mapping geographic information system (GIS) is an innovative Android-based application designed to efficiently assist users in finding the closest route to PAUD schools. By leveraging GPS technology, this system displays a detailed geographic map that guides users effectively through their surroundings. At the core of its functionality is the Dijkstra Algorithm, which ensures the calculation of the shortest path to the desired location, making navigation straightforward and reliable. The design process employs UML (Unified Modeling Language) to create a clear structure and user-friendly interface, enhancing the overall user experience. Developed in Java and supported by the Android Studio platform, this GIS provides essential information about PAUD addresses, their statuses, and available facilities. This comprehensive approach allows users to make informed decisions about educational opportunities for their children. The system has undergone rigorous testing to validate its effectiveness. This practical application demonstrates the system's capability in real-world scenarios and highlights its role in improving access to early childhood education. Furthermore, the PAUD mapping geographic information system is a valuable community resource. By delving into geographic data and providing actionable insights, it aims to bridge gaps in educational access. Ultimately, this GIS is an essential tool for parents and educators, facilitating informed choices and enhancing the journey toward quality education for young learners. Its integration of modern technology with educational accessibility makes it an ultimate resource in fostering early childhood development.